Experimental Study on the Effect of a Cooling System on an Unmanned Surface Vehicle Prototype Using a Zenoah G32FC Engine - Asral; Hanifa, Fadjriya (Universitas Medan Area, 2025)
This study presents a performance test of the cooling system on an unmanned vessel prototype using a Zenoah G32FC engine. The purpose of this research is to evaluate the impact of the cooling system on engine temperature, radiator effectiveness, and vessel speed. The experiment was conducted using a platform supply vessel (PSV) prototype with a monohull design, measuring 120 cm in length and 35.15 cm in width. The Zenoah G32FC engine is a 2-stroke engine with a displacement of 31.8 cc, serving as the main propulsion unit for the prototype. Two types of coolant fluids were tested: water and radiator coolant. The results showed that the use of a radiator helped maintain engine temperature more effectively compared to operating without one, with an average test temperature of 64.3°C and a peak temperature of 71.6°C. The radiator coolant achieved the highest effectiveness, reaching 57.6%, with a heat transfer rate of 341 watts. Vessel speed remained relatively constant throughout all tests, indicating that the use of a radiator had minimal impact on speed, while still maintaining engine temperature within a safe range. Therefore, the use of a radiator is strongly recommended to optimize engine performance.